, 05.06.2022jflandersneongr

# HELP!!! alexisss23

x = 12

y = 1

for the points!  plantkiana677oxa6hk

step-by-step explanation: amandaaaa13

(f - g)(4) = 4

Step-by-step explanation:

f(x) = 3x - 3g(x) = 3x - 4

We can find (f - g)(4) by subtracting the two functions and multiplying the answer by 4.

f - g = (3x - 3) - (3x - 4)f - g = 3x - 3 - 3x + 4 f - g = -3 + 4 f - g = 1

Now, multiply (f - g) by 4 to get the

4(f - g) = 4(1) 4(f - g) = 4

Therefore, (f - g)(4) = 4.  ### Other questions on the subject: Mathematics Mathematics, 21.06.2019, maybrieldridge12
1 x=22.52 2: 65/39=604+39x 65x-39x=604 26x=604 x=604/26 ×=23.23...Read More Mathematics, 21.06.2019, zay65307
step-by-step explanation: this is not a question...Read More  Mathematics, 21.06.2019, kameronstebbins
the answer is 1 becuz if it were 1.0 that would rip apart the entire so ya. : )~potato.copyright potato 2019....Read More Mathematics, 22.06.2019, destinywashere101
area of rectangle a is 2 times that of rectangle b that means 2x+x =   36cm^23x = 36cm ^2x = 36/3 x= 12cm^2and 2x = 24cm^2now side of square = are divided by sides = 36/4 = 6c...Read More   